Reduced salivary flow rate and high levels of oxidative stress in whole saliva of children with Down syndrome - Domingues, Natália Bertolo [UNESP]; Mariusso, Matheus Racy [UNESP]; Tanaka, Marcia Hiromi [UNESP]; Scarel-Caminaga, Raquel Mantuaneli [UNESP]; Mayer, Marcia Pinto Alves; Brighenti, Fernanda Lourenção [UNESP]; Zuanon, Ângela Cristina Cilense [UNESP]; Ibuki, Flávia Kazue; Nogueira, Fernando Neves; Giro, Elisa Maria Aparecida [UNESP] (Wiley, 2017)
Aim: To investigate salivary parameters between children with Down Syndrome (DS) and without DS. Materials and Methods: Stimulated whole saliva was collected from 18 children with DS and 23 without DS. Salivary flow rate, pH, and salivary buffering capacity were determined. Cariogenic microorganisms were quantified by culture, and periodontopathogens by quantitative real-time polymerase chain reaction. The antioxidant profile was quantified spectrophotometrically, while malondialdehyde (MDA) was quantified by high-performance liquid chromatography. Data were analyzed by Mann-Whitney test and Spearman correlation (α = 0.05). Results: Salivary flow rate was significantly lower in DS than in controls (p < 0.0001). Significant higher difference was observed for total protein dosage (p < 0.0001), superoxide dismutase activity (SOD) (p = 0.0002), and MDA (p < 0.001) in DS group. Conclusions: Reduced salivary flow rate might be an important factor in oral diseases development. High salivary levels of SOD and MDA show the significant influence of the oxidative stress and the early-onset periodontal disease in DS people.
Keywords: Down syndrome; periodontal disease; saliva